PTH-094 Thiopurine Adverse Events in patients with Inflammatory Bowel Disease in the UK- IBD BioResource Cohort. (June 2019) - Hong, You Yi; Withanachchi, Achini Diana; Shawky, Rasha; Parkes, Miles
Abstract : Introduction: The Inflammatory Bowel Disease (IBD) BioResource is recruiting patients with Crohn's Disease (CD), Ulcerative Colitis (UC) or IBD type Unclassified (IBDU) from 89 hospitals UK-wide. >19, 000 subjects have been recruited to date. Data have been collected on disease phenotype, treatment, adverse events and treatment response. Aim: To describe the prevalence of adverse events related to thiopurine exposure among the IBD Bioresource cohort Methods: A descriptive, retrospective analysis of the IBD BioResource database has been performed to determine the incidence of short and long-term adverse events related to the use of thiopurines in the treatment of inflammatory bowel disease. All patients who have had exposure to thiopurine therapy (azathioprine or 6-mercaptopurine) were included. Results: 10 092 (57.8%) patients within the IBD BioResource cohort have had some exposure to thiopurine therapy during their disease course, either as monotherapy or in combination with anti-TNF. 9480 patients (94.0%) have been treated with azathioprine (AZA) and 2335 patients (23.1%) have been treated with 6-mercaptopurine (6 MP). Of the 9480 patients who have been treated with azathioprine, 4167 patients (44.0%) remain on this therapy. 2369 patients (24.9%) ceased azathioprine due to adverse events. 1723 of the 2335 (73.8%) patients treated with 6 MP had previously been treated with AZA and been intolerant. 684 patients (29.3%) ceased 6 MP due to adverse events. The most commonly reported adverse events were nausea and vomiting (9.6%), followed by deranged liver function tests (5.1%), non-specified patient intolerance (2.4%), flu like symptoms (2.3%) and abdominal pain (2.3%). The incidence of clinically serious side effects was low. Pancreatitis was reported in 2.2% of patients; and leukopenia (total WCC<3 or neutrophil count<2) was seen in 379 (3.7%). 83 (0.8%) patients developed lymphoma after a mean of 2.9 years on thiopurine treatment. 27/83 were also on anti-TNF. Conclusion: We report a large, real world series of patients with IBD treated with azathioprine or 6 MP. Thiopurines were ceased due to side effects in 25.1% of patients overall. The incidence of adverse events with 6 MP was only modestly higher than in those treated with azathioprine, despite 73.8% having been previously treated with azathioprine. Serious clinical adverse events related to thiopurine exposure were observed but at low frequency.